PENGARUH GAYA KEPEMIMPINAN SITUASIONAL DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BLUE BIRD PEKANBARU - Leo Eperdy; Seno Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This study aims to determine the influence of situational leadership style and work motivation on employee job satisfaction at PT. Blue Bird Pekanbaru. where two independent variables are proposed and one dependent variable, situational leadership style and work motivation as independent variable and employee job satisfaction act as dependent variable. This research method is descriptive and quantitative by using SPSS 21 program, where the sample used is employees of PT. Blue Bird Pekanbaru with 43 respondents. For sampling technique using census method. Technique of collecting data through kusioner and interview. The result of analysis using validity test, reliability test, detemination test, simple linear regression test, multiple linear regression test, t test, and f test so that it can be seen that situational leadership style have a significant effect on employee job satisfaction, that work motivation has significant effect on employee job satisfaction , and that situational leadership style and work motivation have a significant effect on employee job satisfaction. Keywords: Situational Leadership Style, Work Motivation, and Employee Job Satisfaction